Determination of the Managerial Competencies of Clinical Nurse Managers: Self-Assessment - Osman Bilgin; Serap Torun (Association of Nurse Managers, 2023)
Aim: In this study, it was aimed to evaluate the managerial competencies of clinical nurse managers. Method: This descriptive study was conducted with 120 clinical nurse managers working in three different hospitals. Data were collected using the Personal Information Form and the Nursing Supervisor Competency Evaluation Inventory. Results: It was determined that the competence levels of clinical nurse managers differed according to the institutions they were employed in, their managerial experiences, and how they were addressed by their subordinates. In this study, the Cronbach's alpha coefficient of the inventory was 0.97, the total mean score was 202.75 (SD=17.73), the mean score of the overall unit management subscale was 99.69 (SD=8.73), the mean score of the staff management subscale was 67.26 (SD=6.18), and the mean score of the management of care subscale was found to be 35.79 (SD=3.46). Conclusion: The level of management competencies of clinical nurse managers was found to be high. It was determined that the competence levels differed according to the institutions they were employed in, their managerial experiences, and how they were addressed by their subordinates.